Enteral Clostridium difficile, an emerging cause for high-output ileostomy. Issue 10 (15th May 2009) - Williams, R N; Hemingway, D; Miller, A S
Abstract : The loss of fluid and electrolytes from a high-output ileostomy (>1200 ml/day) can quickly result in dehydration and if not properly managed may cause acute renal failure. The management of a high-output ileostomy is based upon three principles: correction of electrolyte disturbance and fluid balance, pharmacological reduction of ileostomy output, and treatment of any underlying identifiable cause. There is an increasing body of evidence to suggest that Clostridium difficile may behave pathologically in the small intestine producing a spectrum of enteritis that mirrors the well-recognised colonic disease manifestation. Clinically this can range from high-output ileostomy to fulminant enteritis. This report describes two cases of high-output ileostomy associated with enteric C difficile infection and proposes that the management algorithm of a high-output ileostomy should include exclusion of small bowel C difficile .